The Analysis of Students' Learning Difficulties in Solving Algebraic Function Derivative Problems in Higher Education - Winsaputri, Kharisma Disti (Journal of Education and Religious Studies, 2025)
The purpose of the study was to describe the Mathematic department students learning dificulties in solving problems related to the Derivative of Algebraic Function method based on mathematical skills, and to identify the contribution factors. This study used a qualitative method to describes the students difficulties in solving derivative problems on algebraic functions. The subject of the study were 5 mathematic education students in their first semester of the 2024/2025 academic year on Calculus 1, Pawyatan Daha University of Kediri. The data collection used test and interview method. The result of the study showed that 60% of students experienced difficulties in arithmatics skill, 40% experienced difficulties in information  skills, and 20% experienced difficulties in number fact skills. The factors that cause these learning difficulties are: 1) Difficulties in arithmatic skills, that is difficulties that caused by students inability to analyzed the appropriate algebraic derivation techniques for a problem  and errors in solving the derivation procedure. 2) Difficulties in number fact skills, that is difficulties caused by don't understanding mathematical operational well, and 3) Difficulties in information skills, that is the difficulties that caused missreading and interpreting the questions.